2020
DOI: 10.3390/geosciences10080283
|View full text |Cite
|
Sign up to set email alerts
|

Neogene Tree Trunk Fossils from the Meshgin Shahr Area, Northwest Iran

Abstract: In 2016, an extensive fossil forest was discovered near Meshgin Shahr, northwest Iran. Silicified tree trunks occur in Miocene fluvial sediments and at multiple stratigraphic levels within a 27-m thick sequence of Pleistocene volcaniclastics. The Miocene trunks likely represent stream transport. Pleistocene examples originated during repeated eruptive events when volcaniclastic sediments buried a standing forest. The site, informally named Meshgin Shahr Fossil Forest, was registered in 2017 as a national natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Megagyrolithes asdescensis is a large spiral burrow attributed to crustaceans (Gaillard, 1980). Myers et al (2019), in an aquaria-based study, reported sedimentary structures resembling planar lamina and ripple cross lamina with grain sizes ranging from fine sand to gravel made by a sand-sifting goby, and they noted that these structures may have a long history in the geological record reflecting feeding styles and bio-resuspension behaviors of macrofauna from different time periods (Myers et al, 2019). Numerous gutter-like furrows, up to 60 cm wide and up to 9 m long, have been reported from the shallow Middle Jurassic sea floor from Liesberg, Switzerland, and interpreted as feeding traces made by large marine vertebrates, most likely plesiosaurs and ichthyosaurs searching for food in the lime mud (Geister, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Megagyrolithes asdescensis is a large spiral burrow attributed to crustaceans (Gaillard, 1980). Myers et al (2019), in an aquaria-based study, reported sedimentary structures resembling planar lamina and ripple cross lamina with grain sizes ranging from fine sand to gravel made by a sand-sifting goby, and they noted that these structures may have a long history in the geological record reflecting feeding styles and bio-resuspension behaviors of macrofauna from different time periods (Myers et al, 2019). Numerous gutter-like furrows, up to 60 cm wide and up to 9 m long, have been reported from the shallow Middle Jurassic sea floor from Liesberg, Switzerland, and interpreted as feeding traces made by large marine vertebrates, most likely plesiosaurs and ichthyosaurs searching for food in the lime mud (Geister, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The processes involved in outer shelf siliceous permineralization are poorly documented but require a generous source of free silica. This might derive from the breakdown of volcanic glass from ash beds intercalated within a sedimentary succession (Maguire et al, 2016), the dissolution of feldspars (Mustoe et al, 2020), or from more exotic sources, such as silica-charged marine seep fluids, and/or dissolution of associated sponge-or radiolarian-rich deposits (Kuechler et al, 2012). In the case of the wood-rich Hauterivian-Barremian Birdrong Sandstone of Western Australia, the source of permineralizing silica may have been from the overlying (Aptian) Windalia Radiolarite.…”
Section: Sixth Stage: Permineralization Of the Woodmentioning
confidence: 99%
“…Especially opal-A is not well recognized in XRD patterns but it appears as an amorphous mineral inoptical and SEM microscopy of some samples of Malkara-Keşan region petrified wood. On the other hand, opal-A formed in petrified wood cells that contain a small quartz-filled fracture produces a pattern that appears to indicate quartz composition (Mustoe et al, 2020).…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…This is not common in fossil wood, but some petrified wood specimens from arid regions include gypsum. The presence of this mineral in silicified wood from the Malkara-Keşan region probably represents a time when ground water contained dissolved sulfate, causing Ca toprecipitate as CaSO 4 rather than as CaCO 3 or Ca 5 (PO 4 ) 3 (Mustoe et al, 2020). If gypsum is present, the Ca:S ratio should be 1:1 (Mustoe, 2021).…”
Section: Scanning Electron Microscopy/energy Dispersive X-ray Spectroscopy (Sem/eds)mentioning
confidence: 99%